2012
DOI: 10.5194/acp-12-10841-2012
|View full text |Cite
|
Sign up to set email alerts
|

On the isolation of OC and EC and the optimal strategy of radiocarbon-based source apportionment of carbonaceous aerosols

Abstract: Radiocarbon (<sup>14</sup>C) measurements of elemental carbon (EC) and organic carbon (OC) separately (as opposed to only total carbon, TC) allow an unambiguous quantification of their non-fossil and fossil sources and represent an improvement in carbonaceous aerosol source apportionment. Isolation of OC and EC for accurate <sup>14</sup>C determination requires complete removal of interfering fractions with maximum recovery. The optimal strategy for <sup>14</sup>C-based sour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
210
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(223 citation statements)
references
References 57 publications
11
210
1
1
Order By: Relevance
“…As a result, the 14 C values of the EC fraction may be incorrect. 30 Although charring can be minimized by performing the water extraction step prior to the thermal treatment, 10,30,31 it is not adequate to separate all of the OC. 16,18 A longer separation duration for the elimination of the OC, for example, 12 and 24 h, was suggested at 375°C in air.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…As a result, the 14 C values of the EC fraction may be incorrect. 30 Although charring can be minimized by performing the water extraction step prior to the thermal treatment, 10,30,31 it is not adequate to separate all of the OC. 16,18 A longer separation duration for the elimination of the OC, for example, 12 and 24 h, was suggested at 375°C in air.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Joint projects covered development of the gas ion source and the gas inlet system (Ruff et al 2007;Wacker et al 2013a), coupling of an elemental analyzer and other combustion instruments with the AMS (Perron et al 2010;Ruff et al 2010), development of sample pretreatment methods and instrumentation for routine 14 C dating (Němec et al 2010ab;) and applications to carbonaceous aerosols in the atmosphere and in glacier ice (Sigl et al 2009;Szidat 2009a,b;Zhang et al 2012). About >2000 unknown gas samples were measured within these projects at the ETH AMS systems until the end of 2012.…”
Section: S Szidat Et Almentioning
confidence: 99%
“…Separation and sample combustion instruments were directly coupled with the gas source (Perron et al 2010;Ruff et al 2010) with applications to carbonaceous aerosols in the atmosphere and in glacier ice (Sigl et al 2009;Szidat 2009a,b;Zhang et al 2012). A particular focus was on building and refining of an automated gas interface (Wacker et al 2013a), which enables the transfer of carbon dioxide to the gas ion source from different sources, such as sealed glass ampoules, an acidification device for carbonate samples (Wacker et al 2013b), as well as an elemental analyzer or other combustion instruments (Perron et al 2010).…”
Section: Instrumentationmentioning
confidence: 99%
“…traffic exhaust emissions and coal burning) sources (Lemire et al, 2002;Szidat et al, 2004Szidat et al, , 2009. The measurement of the 14 C content of total carbon (TC), which comprises the elemental carbon (EC) originating from combustion sources and the organic carbon (OC), had been the subject of many studies (Schichtel et al, 2008;Glasius et al, 2011;Genberg et al, 2011;Zhang et al, 2012Zhang et al, , , 2016Zotter et al, 2014b;Bonvalot et al, 2016). Results have shown that in European sites, especially in Alpine valleys, the non-fossil sources play an important role during winter due to biomass burning and in summer due to biogenic sources (Gelencsér et al, 2007;Zotter et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%